2004
DOI: 10.1002/hbm.20055
|View full text |Cite
|
Sign up to set email alerts
|

Determining the hemispheric dominance of spatial attention: A comparison between fTCD and fMRI

Abstract: Human brain mapping allows the systematic assessment of interindividual differences in functional brain anatomy. Functional transcranial Doppler sonography (fTCD) is an imaging tool that allows for fast and mobile assessment of hemispheric lateralization of task-related brain activation. It is ideal to screen large cohorts of subjects. The goal of the present study was to investigate whether fTCD and functional magnetic resonance imaging (fMRI) determine hemispheric lateralization of brain activation related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 46 publications
2
35
0
Order By: Relevance
“…The degree of laterality expressed in the LIs is dependant on the chosen statistical threshold and should therefore be treated with caution. The approach itself, however, has been shown to produce LIs which are not significantly different from LIs calculated via other means and which correlate well with LIs calculated from Wada and fTCD measurements (e.g., Chelbus et al, 2007;Jansen et al, 2004). In our study, laterality for those participants who were strongly left dominant and those who were strongly right dominant was exceptionally clear, regardless of cut off p-values chosen.…”
Section: Calculationssupporting
confidence: 62%
“…The degree of laterality expressed in the LIs is dependant on the chosen statistical threshold and should therefore be treated with caution. The approach itself, however, has been shown to produce LIs which are not significantly different from LIs calculated via other means and which correlate well with LIs calculated from Wada and fTCD measurements (e.g., Chelbus et al, 2007;Jansen et al, 2004). In our study, laterality for those participants who were strongly left dominant and those who were strongly right dominant was exceptionally clear, regardless of cut off p-values chosen.…”
Section: Calculationssupporting
confidence: 62%
“…Although there has been some question as to the reliability of fMRI-based laterality measures (Jansen et al, 2006), classification of language lateralization based on this task has yielded results consistent with the Wada test, which is thought to be the "gold standard" for measuring hemispheric dominance (Woermann et al, 2003;Yetkin et al, 1998), and also yield results consistent with functional transcranial Doppler sonography (Jansen et al, 2004). Moreover, the test-retest reliability of lateralization has been shown to be high (Adcock et al, 2003;Fernandez et al, 2003).…”
Section: Image Pre-processing and Analysesmentioning
confidence: 90%
“…Hemispheric dominance for language and spatial attention was originally assessed by fTCD (see below), and confirmed by fMRI Jansen et al, 2004a). (Lezak, 1995).…”
Section: Subjectsmentioning
confidence: 99%
“…In a previous study on healthy subjects, we investigated whether functional transcranial Doppler sonography (fTCD) and functional magnetic resonance imaging (fMRI) determine hemispheric dominance of brain activation related to visuospatial attention concordantly (Jansen et al, 2004a). In this study, we identified three subjects who were lefthemisphere lateralized for spatial attention and right-hemisphere dominant for language and two subjects who were right-hemisphere dominant for both language and spatial attention.…”
Section: Introductionmentioning
confidence: 99%